1977
DOI: 10.1063/1.89630
|View full text |Cite
|
Sign up to set email alerts
|

EPR of a thermally induced defect in silicon

Abstract: Two EPR spectra are resolved in quenched silicon; one is attributed to a surface damage formed during the quench and the other to the interstitial iron (Fe0) previously identified by Woodbury and Ludwig in Fe-diffused silicon. The enthalpy and entropy for the Fe0 formation are determined to be 2.39 (±0.03) eV and 3.3 (±0.3) K, respectively. The migration energy of Fe0 is 0.69 (±0.03) eV. The transition-metal ion is present in as-grown silicon and moves to the Td interstitial site upon heat treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…26,27 At low temperature, Fe i ϩ interstitials could be easily captured by negatively charged boron acceptor, Enhanced Gettering of Iron Impurities in Bulk Silicon by Using External Direct Current Electric Field L27 Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…26,27 At low temperature, Fe i ϩ interstitials could be easily captured by negatively charged boron acceptor, Enhanced Gettering of Iron Impurities in Bulk Silicon by Using External Direct Current Electric Field L27 Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…Weber and Riotte [29] measured the iron content by NAA and EPR after diffusion at 1173-1473 K and found a higher content by NAA than by EPR. These observations by Lee et al [28] as well as Weber and Riotte [29] indicates that EPR does not give the total concentration of iron. Isobe et al [30] stud- ied the interstitial iron diffusion into silicon at 1073-1343 K using DLTS but the determined solubility might not correspond to the total iron.…”
Section: Ironmentioning
confidence: 89%
“…It seems that the surface concentration could, however, be influenced by the back diffusion of iron and its piling up during the sample cooling process. Woodbury and Ludwig [17] measured the interstitial iron content by EPR after diffusion at 1473 K. Lee et al [28] measured the interstitial iron content of silicon by EPR after annealing at 1123-1473 K followed by a different cooling process such as quenching with water or liquid nitrogen. They found that iron changes its electronic state during cooling, which indicates that iron exists mostly in the interstitial sites of silicon at high temperatures but occupies substitutional sites or forms defects during the cooling process.…”
Section: Ironmentioning
confidence: 99%
“…The solubility of iron below the eutectic temperature was studied by Lee et al, 42) Mchugo et al, 43) Colas and Weber, 44) Weber, 45) Struthers, 46) Nakashima et al 47) and Gills et al 48) Thermodynamic description of the solid diamond phase was optimized using the above experimental phase equilibrium information. Parameters for the excess Gibbs energy of the liquid Si-Fe phase were optimized by Lacaze and Sundman, 49) based primarily on the assessment by Chart.…”
Section: )mentioning
confidence: 99%